A qualitative examination of choking under pressure in team sport - Hill, D. M.; Shaw, G. (Psychology of Sport and Exercise, 2013)
Objectives: As choking in sport has only been examined to date through athletes performing individual sports and/or closed skills, this study uses a qualitative methodology to provide a unique insight into choking within the team sport setting. Design and methods: Through individual semi-structured interviews, the experiences of eight athletes who choked under pressure regularly whilst playing a team sport were examined in detail. Results: The participants perceived their choking episodes were associated with a range of antecedents, mechanisms, moderators and consequences. Many of which were similar to those found within individual sports/closed skills; although differences were noted. This study supports the suggestion by Hill, Hanton, Matthews, and Fleming (2010a) that choking in sport may be caused by distraction, debilitative anxiety and low perceived control, and that its consequence is a significant drop in performance. Conclusions: The study extends the choking literature and offers information for practitioners working with teams.